PRODUCTION TECHNOLOGY AND NUTRITIONAL EVALUATION OF FISH CUTLETS - Smolnikova, Farida; Kazhybayeva, Galiya; Tsapov, Evgeny; Sharipova, Svetlana; Sharova, Tamara; Nikolaeva, Natalia; Gribkova, Vera; Garipova, Larisa; Terehova, Anna (International Journal of Psychosocial Rehabilitation, 2020)
This paper studies the use of fish in school meals. The production technology and recipe of six samples of fish cutlets with different combinations of laminaria, rice, carrots, nonfat cottage cheese are presented. These components have the effect on the chemical composition and nutritional value of the finished product. According to the results of chemical composition, the protein content varies from 17.02% to 17.53%, fat from 1.80% to 2.73% and carbohydrates from 6.54% to 7.22%. According to the mineral composition, an increased content of calcium (28.51 mg/100g in sample 1 and 22.51 mg/100g in sample 2) was found in fish cutlets with the addition of curd whey (15 to 20 % to the recipe). The variety of the chemical composition and structure of the fish tissue make it an excellent diet product.